Emotional Prosody Effects on Verbal Memory in Euthymic Patients With Bipolar Disorder - Altamura, Mario; Santamaria, Licia; Elia, Antonella; Angelini, Eleonora; Padalino, Flavia A.; Altamura, Claudia; Padulo, Caterina; Mammarella, Nicola; Bellomo, Antonello; Fairfield, Beth (Frontiers in Psychiatry, 2019)
A growing body of evidence suggests that emotional prosody influences the ability to remember verbal information. Although bipolar disorder (BD) has been shown to be associated with deficits in verbal memory and emotional processing, the relation between these processes in this population remains unclear. In the present study, we aimed to investigate the impact of emotional prosody on verbal memory in euthymic BD patients compared to controls. Participants were randomly divided into three subgroups according to different prosody listening conditions (a story read with a positive, negative, or neutral prosody) and effects on a yes–no recognition memory task were investigated. Results showed that euthymic bipolar patients remembered comparable numbers of words after listening to the story with a negative or neutral prosody but remembered fewer words after listening to the positive version compared to healthy controls. Results suggest that verbal memory is hindered in BD patients after listening to the story read with a positive prosody. This recognition bias for information with a positive prosody may lead to negative intrusive verbal memories and poor emotion regulation